THE STATE ANTI-CRISIS STRATEGY, THE TASKS AND RISKS OF MANUFACTURE REINDUSTRIALIZATION - O. Kozhevina (Управленческие науки)
Defining the strategic priorities of Russia economic development is the urgent problem nowadays. The sanctions have negatively influenced all the branches of the economy including the industrial sector. Reindustrialization and diversification are the imperatives of Russia economic stability. The article2 considers the results of researching the processes of reindustrialization and import substitution in the industrial sector. The key issues considered in the article are the following: factors of economic stability and industrial sector, support of import substitution, public regulation and regional industrial strategic management, assessment of industrial sector’s development trends for the last years in comparison with the current conditions of sanctions and restrictions; detecting the „growth zones” and „the zones of faster industrial and technological development”, analysis of institutional and legal framework of realization the state anti-crisis strategy in the sphere of industrial development.Based on the empirical analysis of main indices dynamics of the industrial development in Russia and federal circuits, as well as social and economic situation of the territorial entities of the Federation the risks influencing the real sector efficiency and competitiveness have been detected. It’s useful to take into consideration the mentioned risks in the process of realization the state anti-crisis strategy. The directions of leveling and minimizing the risks have been formulated; the main tasks of state anti-crisis strategy in the sphere of Russia and regions industrial development have been defined. The zones of faster industrial and technological development, the formation of innovative clusters and integrated structures have been detected.